Gagasan Pembaharuan Pendidikan Islam Berkemajuan Perspektif K.H. Ahmad Dahlan - Muaddyl Akhyar; Zulmuqim; Muhammad Kosim (Institut Kariman Wirayudha Sumenep, 2024)
This research aims to analyse how the idea of Islamic education reform progresses from the perspective of K.H. Ahmad Dahlan and the role of Muhammadiyah in inheriting K.H Ahmad Dahlan's thoughts. The method in this research uses character research with a literature study approach (Library Research). The results showed that K.H. Ahmad Dahlan was a reform thinker in Indonesia who was engaged in the field of education through the organisation he formed, namely Muhammadiyah. There are so many thoughts of renewal of Islamic education, such as in the aspects of the education system, educational goals, educational materials to teaching methods. K.H. Ahmad Dahlan as a figure of renewal in Indonesia came up with his thoughts to respond to the condition of the people, especially in the field of Islamic education which was very bad in Indonesia during the Dutch colonial government. The presence of the Islamic organisation formed by K.H. Ahmad Dahlan, Muhammadiyah, also inherited K.H. Ahmad Dahlan's understanding of progressive Islamic education, which is needed to be implemented in Indonesia. The results of this study can also be used as a reference in other studies related to Islamic education in Indonesia